A glutathione peroxidase from Antarctic psychrotrophic bacterium Pseudoalteromonas sp. ANT506: Cloning and heterologous expression of the gene and characterization of recombinant enzyme. Issue 6 (2nd November 2017) - Wang, Yatong; Han, Han; Cui, Bingqing; Hou, Yanhua; Wang, Yifan; Wang, Quanfu
ABSTRACT: A glutathione peroxidase (GPx) gene, designated as Ps GPx, was cloned from Antarctic psychrotrophic bacterium Pseudoalteromonas sp. ANT506 and expressed in Escherichia coli . The full-length Ps GPx contained a 585-bp encoding 194 amino acids with predicted molecular masses of approx. 21.7 kDa. Multiple sequence alignments revealed that Ps GPx belonged to the thioredoxin-like superfamily. Ps GPx was heterologously overexpressed in E. coli, purified and characterized. The maximum catalytic temperature and pH value for recombinant Ps GPx (r Ps GPx) were 30°C and pH 9.0, respectively. r Ps GPx retained 45% of the maximum activity at 0°C and exhibited high thermolability with a half-life of approx. 40 min at 40°C. In addition, the enzymatic activity of r Ps GPx was still manifested under 3 M NaCl. The K m and V max values of the recombinant enzyme using GSH and H2 O2 as substrates were 1.73 mM and 16.28 nmol/mL/min versus 2.46 mM and 21.50 nmol/mL/min, respectively.